دور البيوت التراثية اليهودية في تنمية السياحة بمدينة عقرة - كوردستان العراق )بيت هاشم احمد قاسم جوستەيە( - د.اراس اسماعيل خضر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
It is no secret to anyone that the development Heritage Houses Jewish tourist aims at contributing to the increase in real national income and provide jobs for the unemployed and the operation of labor as well as providing hard currency and restore the infrastructure of the regions qualifying all Hence the development of tourism as a means of economic development and this follow-up based economic development the tourism sector to varying degrees in increasing the national income and real per capita income by paying tourist variables in the community to grow faster than the natural growth rate, that tourism development is in this case growth involuntarily driven, and there are many indicators of this growth in international tourism sector, perhaps in particularly the increasing number of tourists and the number of tourist nights and tourist spending and revenues in the tourist town of Aqra.